The relationship between severity of drug problems and perceived interdependence of drug use and sexual intercourse among adult males in drug addiction rehabilitation centers in Japan - Risa Yamada; Takuya Shimane; Ayumi Kondo; Masako Yonezawa; Toshihiko Matsumoto (BMC, 2021)
Abstract Background Consuming drugs in conjunction with sexual intercourse may shape the perceived interdependence of drug use and sexual intercourse (PIDS). Additionally, the severity of drug problems may have a significant impact on PIDS. However, this relationship remains unverified. Therefore, this study investigates whether the severity of drug problems is associated with PIDS among adult males in drug addiction rehabilitation centers (DARC) in Japan. Methods This study was a secondary analysis of the "DARC Follow-Up Study in Japan" conducted by the National Center of Neurology and Psychiatry in 2016, in which participants from 46 facilities completed a self-report questionnaire. A total of 440 males with drug dependence were included in the analysis. We analyzed participants' demographic characteristics, history of sexually transmitted disease diagnoses, and responses to questions related to drug use (e.g., primary drug use and PIDS). Additionally, we measured the severity of drug problems using the Japanese version of the Drug Abuse Screening Test-20 (DAST-20). Results The median age of the participants was 42 years. The median DAST-20 score was 14.0, the primary drug was methamphetamine (61.4%) and new psychoactive substances (NPS: 13.6%). Multivariate analysis indicated that participants' experiences with unprotected sexual intercourse ("mostly a non-condom user": adjusted odds ratio (AOR) = 4.410), methamphetamine use (AOR = 3.220), new psychoactive substances use (AOR = 2.744), and the DAST-20 score (AOR = 1.093) were associated with PIDS. Conclusions This study indicated that the frequency of unprotected sexual intercourse under the influence of drugs, methamphetamine and NPS use were strongly associated with PIDS. The severity of drug problems was also significantly associated with PIDS. It is necessary to develop culturally appropriate treatment programs adapted to the needs of patients who experience strong PIDS.